the THE RELATIONSHIP BETWEEN THE USE OF THE AUSTRALIAN TRIAGE SCALE METHOD AND PATIENT SATISFACTION IN THE EMERGENCY INSTALLATION OF LEMBANG REGIONAL HOSPITAL, WEST BANDUNG REGENCY IN 2025 - Haryanto, Mokhamad Sandi; Aprilia, Putri (Jurnal Keperawatan Muhammadiyah, 2025)
Background Patient satisfaction is one of the important indicators in assessing the quality of hospital services which is influenced by various factors, one of which is the accuracy and speed of service obtained by the Emergency Department (ER). The initial examination determines the type of emergency care used to describe the concept of rapid and focused assessment to ensure the most efficient use of staff, equipment and facilities for people who need care. Triage is an effort to select victims before being handled, based on the level of emergency, One of the methods used is the Australian Triage Scale (ATS). Objective: To determine the relationship between the use of the Australian Triage Scale Triage Method and patient satisfaction in the Emergency Department of Lembang Regional Hospital, West Bandung Regency in 2025. The design method used was descriptive-correlation with a cross-sectional method, with a population of patients visiting the Emergency Room of Lembang Regional Hospital. The sample size was 95 people, and the sampling in this study used accidental sampling in accordance with the inclusion criteria. This data was collected using an instrument consisting of 15 questions to determine the level of patient satisfaction and an observation sheet to determine whether or not triage was used. Results: Bivariate analysis using the Chi-Square test showed a significant relationship between the use of the Australian Triage Scale triage method and patient satisfaction (p-value 0.007). Conclusion: In this study, there is a relationship between the use of the Australian Triage Scale triage method and patient satisfaction in the Emergency Room of Lembang Regional Hospital, West Bandung Regency. Keywords: patient satisfaction, Emergency Room, Triage. References: (6 books, 11 journals)